Cr(VI) Removal Using A Dual Chamber Microbial Fuel Cell - Ferdinand, Julian; Yuniarto, Adhi (Sainteknol : Jurnal Sains dan Teknologi, 2024)
Chromium ions is notably a hazardous heavy metal due to its toxic and carcinogenic nature, particularly in its hexavalent form, Cr(VI). One of the major Cr(VI) pollution source is from electroplating industry effluent, which may contain high concentrations that pose a risk of contamination of aquatic and soil ecosystems if not treated carefully. One of the alternative method known to be able to treat Cr(VI) wastewater is by using microbial fuel cell (MFC). This research focused on on the removal of Cr(VI) from synthetic electroplating wastewater using a 4L dual-chamber MFC under fed-batch condition, as well as investigating the impact of mixed liquor suspended solids (MLSS) and chemical oxygen demand (COD) concentrations to its performance. Observed parameters include the efficiency of Cr(VI) removal and power density. Septage sludge and acetate were both used as biomass and substrate source respectively. Based on this research, it can be concluded that the highest Cr(VI) removal efficiency and power density were achieved using specific MLSS and COD concentration that resulting in F/M ratio of 0,459 to 0,489 gCOD/gMLSS. From initial Cr(VI) concentration of 50 mg/L, the highest removal was obtained by MFC running with initial MLSS and COD concentrations of 3.500 and 1.500 mg/L respectively, achieving 62,17% over 312 hours. This setup also produced the highest power density of 48,22 mW/m².